Student teachers’ learning-to-teach patterns: connecting teaching approaches, teacher intentions, and self-perceived instructional impact - Tiilikainen, Mikko; Toom, Auli; Lepola, Janne; Husu, Jukka (Informa UK Limited; Taylor & Francis Group, 2025)
This study introduces a comprehensive learning-to-teach (LTT) framework that incorporates three previously unconnected domains: teaching approaches, teacher intentions, and self-perceived instructional impact. The framework is used in research that was conducted in a Finnish comprehensive school setting involving 45 student teachers (STs) during their practicum. STs’ critical teaching incidents and stimulated recall interviews (f = 90) were analyzed through the three LTT domains. The results revealed four key LTT patterns: effective curriculum portrayal through direct teaching approaches, difficulties in student behavior management with one-way teaching approaches, and mixed outcomes in student participation and personal needs accommodation through multi-way direct teaching approach. The study offers insights into diverse LTT patterns. It underscores that STs demonstrate potential in employing interactive direct teaching approach, whereas greater emphasis should be placed on classroom management when using constructivist teaching approaches. The LTT framework is suggested as a promising tool to enhance STs’ learning to teach.